Infective Larvae of Haemonchus contortus (Nematoda: Trichostrongylidae) Are Captured and Destroyed by Nematode-Trapping Fungi Dactylellina spp. (Fungi: Orbiliales) - Manuel Salvador Balanzar-Aguilera; Enrique Gutiérrez-Medina; Gustavo Pérez-Anzúrez; Edgar Jesús Delgado-Núñez; María Eugenia López-Arellano; Ana Yuridia Ocampo-Gutiérrez; Pedro Mendoza-de Gives (Parasitologia)
This study aimed to explore and identify soil-dwelling nematophagous fungi (NF) from the “El Texcal” Ecological Reserve in Morelos, Mexico, and evaluate their potential as biological control agents against Haemonchus contortus infective larvae (HcL3), a major parasitic threat in livestock systems. The fungi were isolated from soil using the sprinkling of soil on water agar plates. The identification of NF was achieved using morphological identification keys, which was corroborated by molecular procedures using the PCR technique in the ITS4 and ITS5 regions. The nematocidal effects occasioned by these NF were examined through their predatory activity (PA) against HcL3 on water agar plates, and additionally, the larval mortality attributed to their liquid filtrates (LFs) was assessed at three different concentrations (25, 50, and 100 mg/mL) on 96-well microtiter plates. Two NF were identified and classified as two species of Dactylellina genus, namely D. haptospora (Dh) and D. phymatopaga (Dp). The PA exhibited by these NF were 94.79% for Dh and 68.88% for Dp; while their LFs showed 27.83% mortality for Dh and 32.86% for Dp at the highest concentration assessed. While the PA was notably high, the moderate larvicidal effect of the LF suggests that their efficacy may primarily rely on direct physical interaction rather than metabolite-mediated toxicity. The high PA demonstrated by these two isolates of NF indicates that they could be effective candidates for biological control agents against HcL3.